Investigating gender differences in the factor structure of the Gudjonsson Compliance Scale - Drake, Kim E.; Egan, Vincent (Wiley, 2017)
Purpose: The Gudjonsson Compliance Scale (GCS) remains, in terms of its psychometrics, an under-researched instrument, in which gender differences in particular have been insufficiently examined. The aim of this research was to therefore investigate the effect of gender on the factor structure of the GCS.